Production of biomass and lipids by the oleaginous microalgae Monoraphidium sp. QLY-1 through heterotrophic cultivation and photo-chemical modulator induction. (July 2016) - Zhao, Yongteng; Li, Dafei; Ding, Ke; Che, Raoqiong; Xu, Jun-Wei; Zhao, Peng; Li, Tao; Ma, Huixian; Yu, Xuya
Highlights: High biomass and lipid contents were achieved within a short life cycle. Lipid productivity in 5 mM GB-treated samples significantly increased than control. A two-step strategy was developed for algal biomass and lipid production. Abstract: A two-step strategy comprising heterotrophic cultivation and photo-chemical modulator induction was developed to enhance biomass and lipid accumulation in the oleaginous Monoraphidium sp. QLY-1, which was isolated from Qilu Lake in Yunnan Plateau. The algae were first cultivated heterotrophically to achieve high biomass concentration (5.54 g L −1 ) with a lipid content of 22.47%. The cultivated algae were diluted, transferred to light environment, and treated with different chemical elicitors. Results showed that the lipid content increased to 36.68% after 3-day of photoinduction. The lipid content was further enhanced by 1.21, 1.32, and 1.29 folds in algal cells treated with nitrogen deficiency, 20 g L −1 NaCl, and 5 mM glycine betaine, respectively. The maximum lipid content (48.54%) and lipid productivity (121.27 mg L −1 d −1 ) were obtained in treatments with 20 g L −1 NaCl and 5 mM GB, respectively. This study proposes a strategy to efficiently produce lipids by using microalgae.